Macrophage Control of Incipient Bone Formation in Diabetic Mice - Kang, Miya; Thalji, Ghadeer; Huang, Chun-Chieh; Shirazi, Sajjad; Lu, Yu; Ravindran, Sriram; Cooper, Lyndon F. (Frontiers in Cell and Developmental Biology, 2021)
Both soft and hard tissue wound healing is impaired in diabetes. Diabetes negatively impacts fracture healing, bone regeneration and osseointegration of endosseous implants. The complex physiological changes associated with diabetes often manifest in immunological responses to wounding and repair where macrophages play a prominent role in determining outcomes. We hypothesized that macrophages in diabetes contribute towards impaired osseous wound healing. To test this hypothesis, we compared osseous wound healing in the mouse calvaria defect model using macrophages from C57BL/6J and db/db mice to direct osseous repair in both mouse strains. Initial analyses revealed that db/db mice macrophages showed an inflamed phenotype in its resting state. Incipient bone regeneration evaluated by μCT indicated that bone regeneration was relatively impaired in the db/db mouse calvaria and in the calvaria of C57BL/6J mice supplemented with db/db macrophages. Furthermore, osteogenic differentiation of mouse mesenchymal stem cells was negatively impacted by conditioned medium from db/db mice compared to C57BL/6J mice. Moreover, miRNA-Seq analysis revealed an altered miRNA composition in db/db macrophages with up regulated pro-inflammatory miRNAs and down regulated anti-inflammatory miRNAs. Overall, this study represents a direct step towards understanding macrophage-mediated regulation of osseous bone regeneration and its impairment in type 2 diabetes mellitus.